2019
DOI: 10.1590/1807-1929/agriambi.v23n9p655-661
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic and nutritional properties and drying kinetics of pequi (Caryocar brasiliense Cambess) mesocarp

Abstract: The objectives of this study were to fit mathematical models to the experimental data of the drying of the pequi mesocarp, determine the effective diffusion coefficient, and to obtain activation energy and thermodynamic and nutritional properties in different drying conditions. The mesocarp of pequi fruits, with an initial moisture content of 5.05 (decimal, dry basis), was dried in a forced ventilation oven at temperatures of 40, 50, 60 and 70 °C until the final moisture content of 0.15 ± 0.01 (decimal, dry ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
1
4
0
1
Order By: Relevance
“…They found that the time spent for drying at 50°C was more than twice the time spent at 70°C. The increase in temperature promoted a decrease in moisture content in a shorter time, which was also verified by Reis et al (2023) for pineapple peel, Oliveira et al (2018) for baru mesocarp, and Souza et al (2019) for pequi mesocarp.…”
Section: Resultssupporting
confidence: 77%
“…They found that the time spent for drying at 50°C was more than twice the time spent at 70°C. The increase in temperature promoted a decrease in moisture content in a shorter time, which was also verified by Reis et al (2023) for pineapple peel, Oliveira et al (2018) for baru mesocarp, and Souza et al (2019) for pequi mesocarp.…”
Section: Resultssupporting
confidence: 77%
“…A literatura cita valores de proteínas para pupunha desidratada sem casca e com casca, variando na faixa de 4,1 a 6,6% (Goia et al, 1993;Kaefer et al, 2013), resultados próximos aos encontrados no presente estudo. Souza et al (2019), desidratando frutos de pequi a diferentes temperaturas de secagem, 40, 50, 60 e 70 o C, cita que a temperatura de 60 o C, não afetou a concentração de proteínas do mesocarpo do fruto, mantendo assim, sua qualidade nutricional.…”
Section: Proteínas Totaisunclassified
“…Negative entropy values indicate the presence of chemical adsorption and/or structural modifications of the adsorbent, as well as that the drying processes are entropically unfavorable [65]. Similar behavior was also observed in the drying of achachairu (Garcinia humilis) peels [63], mesocarp of baru (Dipteryx alata Vogel) [66], and mesocarp of pequi (Caryocar brasiliense Cambess) [67].…”
Section: Resultsmentioning
confidence: 53%